SOLUTION
Write out the expression
![\begin{gathered} \sum ^3_(k\mathop=1)\lbrack1^k+(-1)^k\rbrack \\ \text{This implies k=1,2,3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jhdc6hu0xcxvbrq9jx8mg2clnk8ydwgsmh.png)
Then we substitute k=1 into the expression and obatin the value
![\begin{gathered} k=1 \\ \lbrack1^1+(-1)^1\rbrack=\lbrack1+(-1)\rbrack=\lbrack1-1\rbrack=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awfn4rg12o7t5kbdapabmo4g2mdtm230r4.png)
Similarly,
![\begin{gathered} k=2 \\ \lbrack1^2+(-1)^2\rbrack=\lbrack1+(1)\rbrack=\lbrack1+1\rbrack=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tfk3ncdd2k9d6tnr7h8ejjbtmn1pijncut.png)
Then we also substitute the last value of k
![\begin{gathered} k=3 \\ \lbrack1^3+(-1)^3\rbrack=\lbrack1+(-1)\rbrack=\lbrack1-1\rbrack=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p0czmax08cvaofn9tfrhzt1ytuj4azno45.png)
finally, we take the sum of the result
![\begin{gathered} 0+2+0=2 \\ \text{hence } \\ \sum ^3_{k\mathop{=}1}\lbrack1^k+(-1)^k\rbrack=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p8e87bucct5b22f63krdtmxnoscd6pf5ms.png)
Therefore the summation of the expression from 1 to 3 for the values of k is 2
The right option is E (2).